Evidence for adenoma-carcinoma sequence in the duodenum of patients with familial adenomatous polyposis. The Leeds Castle Polyposis Group (Upper Gastrointestinal Committee). Issue 8 (August 1994) - Spigelman, A D; Talbot, I C; Penna, C; Nugent, K P; Phillips, R K; Costello, C; DeCosse, J J
Abstract : AIMS--To explore the association between duodenal adenoma and carcinoma in patients with familial adenomatous polyposis (FAP). METHODS--A multicentre survey of 1262 patients with FAP yielded 47 cases of duodenal cancer. The association between adenoma and cancer was assessed in these cases. RESULTS--Adenomatous tissue was found within duodenal cancer in 29 of 44 (66%) patients with FAP and in mucosa adjacent to duodenal cancer in 31 of 42 (73%) such patients. Adenomas were found as a component of, or adjacent to, duodenal cancer in 38 of 45 (84%) patients. CONCLUSIONS--These observations support the existence of the adenomacarcinoma sequence in the duodenum of patients with FAP. Factors associated with malignant change included villous histology, moderate or severe dysplasia, and the presence of stage IV duodenal polyposis.